Characterizing Protein Kinase Substrate Specificity Using the Proteomic Peptide Library (ProPeL) Approach. Issue 2 (19th June 2018) - Lubner, Joshua M.; Balsbaugh, Jeremy L.; Church, George M.; Chou, Michael F.; Schwartz, Daniel
Abstract: Characterizing protein kinase substrate specificity motifs represents a powerful step in elucidating kinase‐signaling cascades. The protocol described here uses a bacterial system to evaluate kinase specificity motifs in vivo, without the need for radioactive ATP. The human kinase of interest is cloned into a heterologous bacterial expression vector and allowed to phosphorylate E. coli proteins in vivo, consistent with its endogenous substrate preferences. The cells are lysed, and the bacterial proteins are digested into peptides and phosphoenriched using bulk TiO2 . The pooled phosphopeptides are identified by tandem mass spectrometry, and bioinformatically analyzed using the pLogo visualization tool. The ProPeL approach allows for detailed characterization of wildtype kinase specificity motifs, identification of specificity drift due to kinase mutations, and evaluation of kinase residue structure‐function relationships. © 2018 by John Wiley & Sons, Inc.